Seasonal variation of catalase and heavy metal enzyme (Pb, Cd, Ni) in Pinctada radiata in Persian Gulf, Iran - Asgari, Elahe Ali; Moradi, Ali Mashinchian; Ehteshami, Fariborz; Jamili, Shahla; Rabbani, Mohammad (International Network for Natural Sciences, 2015)
We have different possibilities and tools to assess the impact of pollution on marine ecosystems. The ecotoxicological approaches are based on the use of biomonitors and biomarkers. The purpose of our study was to evaluate the antioxidant enzyme catalase (CAT) as biomarkers in an edible species, Pinctada radiata (Mollusca, Bivalvia) associated with the environmental pollution(heavy metal, Cd, Pb, Ni) in the Persian gulf. Samples were collected seasonly from march 2012 till march 2013 at three station in the Persian gulf (Nakhilo, Hendorabi and lavan Islnad). Mollusc bivalves (Pinctada radiata) with the same shell length (40-50mm) were collected from the sampling sites, transferred to the laboratory and dissected the same day. The mantle was dissected and samples were prepared for biomarker analyses and measuring the heavy metal in soft tissue. The enzyme concentration were determined by using standard methods. Biochemical data showed a no significant The results concluded from the amount of heavy metals in the sediment and soft tissue of pearl oyster(pinctada radiata) show no significant correlation with the level of catalase enzyme. The present study strongly suggests that monitoring programs should compare sites with similar physicochemical characteristics when using a complementary biomarker approach.